The Influence Of Hedonic Motivation Style On Purchasing Decisions With Price As A Moderating Variable : Penelitian - Bambang Suryo Wibowo; Daru Putri Kusumaningtyasi; Herry Syafrial; Yunada Arpan; Robby Mamusung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a quantitative research with an explanatory approach, namely an approach that relies on previous research as the main material for building hypotheses and proving them in the research being conducted. The data used in this study are primary data that researchers obtained from three hundred and forty Uniqlo buyers spread throughout Indonesia. The data obtained by researchers were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the hypothesis proposed by researchers in this study is successful and the other is not. In the first hypothesis, the results of the third table above show that the Hedonic Shopping Motivation variable can have a positive relationship direction and a significant influence on Purchasing Decisions because the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.009. This result is because someone who has the Hedonic Shopping Motivation trait does not care about how much money is spent and how useful the goods consumed are. This can ultimately have an impact on Purchasing Decisions. However, in the next hypothesis, the Price variable is positive but is not below the significance level of 0.05, namely 0.065. These results indicate that someone who has the Hedonic Shopping Motivation trait does not think about price in deciding to buy. Thus, it can be concluded that the first hypothesis in this article can be accepted and the second hypothesis in this article cannot be accepted.